"In Silico" Characterization of 3-Phytase A and 3-Phytase B from Aspergillus niger. (20th November 2017) - Niño-Gómez, Doris C.; Rivera-Hoyos, Claudia M.; Morales-Álvarez, Edwin D.; Reyes-Montaño, Edgar A.; Vargas-Alejo, Nury E.; Ramírez-Casallas, Ingrid N.; Erkan Türkmen, Kübra; Sáenz-Suárez, Homero; Sáenz-Moreno, José A.; Poutou-Piñales, Raúl A.; González-Santos, Janneth; Arévalo-Galvis, Azucena
Abstract : Phytases are used for feeding monogastric animals, because they hydrolyze phytic acid generating inorganic phosphate. Aspergillus niger 3-phytase A (PDB: 3K4Q) and 3-phytase B (PDB: 1QFX) were characterized using bioinformatic tools. Results showed that both enzymes have highly conserved catalytic pockets, supporting their classification as histidine acid phosphatases. 2D structures consist of 43% alpha-helix, 12% beta-sheet, and 45% others and 38% alpha-helix, 12% beta-sheet, and 50% others, respectively, and pI 4.94 and 4.60, aliphatic index 72.25 and 70.26 and average hydrophobicity of −0, 304 and −0.330, respectively, suggesting aqueous media interaction. Glycosylation and glycation sites allowed detecting zones that can affect folding and biological activity, suggesting fragmentation. Docking showed thatH 59 andH 63 act as nucleophiles and thatD 339 andD 319 are proton donor residues. MW of 3K4Q (48.84 kDa) and 1QFX (50.78 kDa) is similar; 1QFX forms homodimers which will originate homotetramers with several catalytic center accessible to the ligand. 3K4Q is less stable (instability index 45.41) than 1QFX (instability index 33.66), but the estimated lifespan for 3K4Q is superior. Van der Waals interactions generate hydrogen bonds between the active center and O2 or H of the phytic acid phosphate groups, providing greater stability to these temporal molecular interactions.